Persistence and management of dinitroaniline herbicides residues in sandy loam soil. (4th December 2009) - Rathod, P.H.; Patel, R.B.; Jhala, Amit J.
The addition of organic manure affects the biological, chemical and physical properties of soil that control the fate of herbicides. Three dinitroaniline herbicides were studied to asses their persistence, dissipation and residue management in sandy loam soil with and without addition of farmyard manure (FYM) under middle western Indian agro-climatic conditions. The herbicides, pendimethalin [N-(1-ethylpropyl)-3, 4-dimethyl-2, 6-dinitrobenzenamine], trifluralin [2, 6-dinitro-N, N-dipropyl-4-(trifluoromethyl) benzenamine] and fluchloralin [N-(2-chloroethyl)-2, 6-dinitro-N-propyl-4-(trifluoromethyl) benzenamine], were applied at a rate of 0.5 and 1.0 kg ha−1 as a pre-plant incorporation in the field, cropped with Indian mustard (Brassica juncea L.). FYM incorporation at a rate of 10 t ha−1 decreased herbicide persistence in all the sampling intervals. Relatively lower half-lives of 44.93, 41.81; 41.23, 39.09 and 39.61, 43.00 days, each at the rate of 0.5 and 1.0 kg ha−1, respectively for pendimethalin, trifluralin and fluchloralin were recorded with FYM incorporation. On the other hand, the half-life values in absence of FYM were higher for all three dinitroaniline herbicides used. Dissipation rate of all three dinitroanilines increased progressively with time at both application rates.